Epigenetic modifications of mRNA and DNA in plants - Liang, Zhe; Riaz, Adeel; Chachar, Sadaruddin (Molecular plant, 2020)
Advances in the detection and mapping of messenger RNA (mRNA) N6-methyladenosine (m6A) and 5-methylcytosine (m5C), and DNA N6-methyldeoxyadenosine (6mA) redefined our understanding of these modifications as additional tiers of epigenetic regulation. In plants, the most prevalent internal mRNA modifications, m6A and m5C, play crucial and dynamic roles in many processes, including embryo development, stem cell fate determination, trichome branching, leaf morphogenesis, floral transition, stress responses, fruit ripening, and root development. The newly identified and widespread epigenetic marker 6mA DNA methylation is associated with gene expression, plant development, and stress responses. Here, we review the latest research progress on mRNA and DNA epigenetic modifications, including the detection, dynamics, distribution, functions, regulatory proteins, and evolution, with a focus on m6A, m5C, and 6mA. We also provide some perspectives on future research of the newly identified and unknown epigenetic modifications of mRNA and DNA in plants.
Available online 18 December 2019
Gesehen am 04.02.2020